Penerapan Self Assesment System PPh Pasal 21 Untuk UMKM - Rita Nataliawati; Umar Yeni Suyanto; Hilda Julfi Hikmawan; Melisa Husniyyah (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2024)
Article 21 Income Tax Income Tax is one of the tax obligations that must be applied in companies. Many Micro, Small and Medium Enterprises (MSMEs) have not applied proper tax treatment in running their business. This activity aims to provide accurate information to Micro, Small and Medium Enterprises (MSMEs), especially for Income Tax Article 21. The implementation of this community service activity is carried out using an interactive discussion approach. Therefore, ITB Ahmad Dahlan Lamongan D3 Tax Study Program implemented a Community Service program (PKM) with the activity title